Leadership, Authority and Representation in British Muslim Communities - Gilliat-Ray, Sophie; Timol, Riyaz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The contributions explore Muslim religious leadership in multiple forms and settings. While traditional authority is usually correlated with theology and piety, as in the case of classically trained ulema, the public advocacy of Muslim community concerns is often headed by those with professionalized skillsets and civic experience. In an increasingly digital world, both women and men exercise leadership in novel ways, and sites of authority are refracted from traditional loci, such as mosques and seminaries, to new and unexpected places. This collection provides systematic focus on a topic that has hitherto been given rather diffuse consideration. It complements historical work on community leadership as well as more contemporary discussion on the training and role of Islamic religious authorities. It will be of interest to scholars in Religious Studies, Sociology, Political Science, History, and Islamic Studies.